Understanding Taxpayer Behavior: A Qualitative Investigation Into Compliance Among Individual Taxpayers - Bilqis Tarwiyah (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This study aims to explore the compliance s employed by individual taxpayers. The research adopts a descriptive research model to understand the intricacies of taxpayer behavior. A purposive sampling technique is utilized to select participants with diverse backgrounds and experiences in tax compliance. Data analysis involves thematic analysis to identify patterns and themes in taxpayer behavior. The findings shed light on the various strategies individuals employ to fulfill their tax obligations, providing insights into factors influencing compliance behavior.